Optimasi Travelling Salesman Problem Pada Angkutan Sekolah Menggunakan Algoritme Genetika (Studi Kasus : Sekolah MI Salafiyah Kasim Blitar) - Ivarianti Sihaloho; Imam Cholisoddin; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Most aspects in all sectors are now fundamentally dependent on the information technology. One of the aspect is about the quality of school services for students, like school bus service. School bus service is one of the efficient school service to support safety for children while their parents are busy to pick up them at school. This is one of the reason from the imporovement of MI Salafiyah Kasim school Bus service for children by optimizing the school bus routes. The Optimization system is built on with Traveling Salesman Problem (TSP) and genetic algorithm methods. MI Salafiyah Kasim school bus service has morning and afternoon arrival and departure of students. The actual road data used in this research consist of the sample within 3 days. This data will be compared to find out and show what method needs less time in comparison with known methods and so efficient for such problem. Based on the data research, the optimization results in the morning departure is about 5.5 km (accuracy = 19.78%) and in the afternoon arrival is about 17.17 km (accuracy = 36.30%). It can be concluded that this system is running well by producing a good optimal value.